Reasons Behind Morals: Moral Teaching in Chinese Context - Ma, Wen; Zhu, Yaqin; Chunli, Li; Zhang, Bo; Tian, Xin (Advances in Social Sciences Research Journal, 2024)
The contents of moral may differ; they require each one to practice. When we know the contents, we do not perform them, then we cannot tell others that we are familiar with them. When we know that we will practice them, yet we lack the knowledge and self-restraint to practice them, we are prevented from fulfilling them. Those who hold wicked thoughts will not perform righteousness; those who have selfish minds will not serve the public. Those who deceive themselves cannot gain trust from others. Those who humiliate themselves cannot earn others’ respect. Thus, in this paper, we discuss three topics of culture and luxury, truth and myth, and following reasons and fearing authority, so that the contents of moral education will be clarified. What is good and bad will be shown. Once we understand reasons, we begin the journey of self-cultivation.